Influence of temperature and pH on induction of Shiga toxin Stx1a in Escherichia coli - Castro, Vinicius Silva; Ngo, Skyler; Stanford, Kim (Frontiers in Microbiology, 2023)
Shiga toxin-producing strains represent pathogenic group that is of concern in food production. The present study evaluated forty-eight E. coli isolatesstrains (11 strains with intact stx gene, while remaining isolatesstrains presented only stx-fragments) for Shiga toxin production. The four most expressive stx-producers (O26, O103, O145, and O157) were selected to evaluate effects of pH (3.5, 4.5, and 7) and temperature (35, 40, and 50℃). After determining the acid stress effects in media onin the stxStx-induction, we mimicked “in natura” conditions using milk, apple, and orange juices. Only isolatesstrains that showed the presence of intact stx gene (11/48) produced Shiga toxin. In addition, acid pH had a role in down-regulating the production of Shiga toxin, in both lactic acid lactic and juices. In contrast, non-lethal heating (40℃), when in neutral pH and milk, it was a favorable environment to induce Shiga toxin. Lastly, two isolatesstrains (O26 and O103) showed a higher capacity to produce Shiga toxin and wereas included in a genomic cluster with other E. coli involved in worldwide foodborne outbreaksworldwide. The induction of this toxin when subjected to 40℃ may represent a potential risk to the consumer, since the pathogenic effect of oral ingestion of Shiga toxin has already been proved in an animal model.